Gendered capital: emotional capital and mothers' care work in education - O'Brien, Maeve (British journal of sociology of education, 2008)
This paper is concerned with the inequalities experienced by mothers in the performance of educational care work for their children. It is argued that the caring work carried out by mothers at transfer to second-level schooling is shaped by their ability to activate the significant resource of emotional capital; a gendered resource involving emotional skills, knowledge and experiences. Drawing on an in-depth study of mothers' routines of care, it is suggested that the possession of emotional capital subjects mothers to a normative order of care. Moreover, in exploring the idiosyncratic differences between mothers' capacities to activate emotional capital it is argued that the activation of this care resource is facilitated in the context of solidary relationships but also by mothers' access to other capitals. It is concluded that in order to tackle care inequalities those working in education need to recognise the significance of emotional resources, and need to challenge traditional codes of practice and policies around 'parental' involvement.